Downscaling of Soil Moisture Map using Sentinel Radar Satellite Images and Distribution Analysis in the West of Iran - Seyed Hossein Mirmosavi; kohzad Raispour; Muhammad Kamangar (جغرافیا و پایداری محیط)
Soil surface moisture is a key variable to describe drought, water and energy exchanges between the earth and the air. Due to the instability of spatial and temporal conditions, the environmental parameters affecting it are highly variable. The current study aims to downscale and extract the soil moisture distribution map with high resolution and its spatial analysis in the west of Iran. An educational layer was created by using the post-scattering bands of VV and VH polarizations as well as the angle of collision band (𝜃) extracted from Sentinel 1 radar images and land use extracted from MODIS sensor. Long-term average moisture per pixel of GLDAS data was also used. The micro-scale backup machine vector algorithm and the high volume resolution soil moisture dispersion map were estimated between 0.18 and 0.46 b. Field data collected from 38 sample farms of Kurdistan Agricultural Research Center were used to verify the output map, which was calculated to be R2 = 0.5012. The results were obtained for the elliptical direction of three times the standard spatial deviation of the northwest to the southeast, which shows that more than 99% of the moisture distribution is expanded in accordance with the spatial arrangement of the heights in this direction. Statistics of 0.3978 Moran index and P_Value value of 0.0000 showed spatial autocorrelation of soil moisture. The hot spot map also showed that the soil surface moisture is nuclear in the northwest and southeast directions and more at altitudes above 2000 meters. Hot spot analysis also reveal that the moisture has strongly clustered to the east and inside the country. Using the obtained spatial analysis results, low or high soil moisture areas can be identified in order to identify environmental potentials and improve the decision-making process, allocation and spatial distribution of services.